2020
DOI: 10.1016/j.heliyon.2020.e03537
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and antimicrobial resistance of Campylobacter spp. in animals in Sub-Saharan Africa: A systematic review

Abstract: Introduction: Low sanitary conditions characterize the rural and urban households in Sub-Saharan African region. Those environmental conditions propitiate the transmission of bacterial infections between animals and humans. Campylobacter spp. is a zoonotic bacterium and cause of human gastroenteritis worldwide, whose main symptom is diarrhea. It is normally found in the digestive tract of many farm animals as a commensal but some species cause diseases in animals. It is important to understand the occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 73 publications
(111 reference statements)
2
22
1
Order By: Relevance
“…Previous findings from Tanzania reported that poultry farming is associated with uncontrolled use of both human and veterinary antimicrobials, mainly for growth promotion compared to therapeutics, and metaphylaxis is very commonly practiced by the majority of farmers [ 24 , 52 ]. The level of resistance to these tested antibiotics for isolates from poultry corresponds to previous studies [ 50 , 53 , 54 ], showing poultry farming involves intensive and extensive use of antibiotics compared to other domestic animals. Tetracycline, aminoglycosides, penicillin, quinolone, and sulphonamides are among the antibiotics reported to be commonly used in poultry in Ghana, Cameroon, and Sudan [ 55 , 56 , 57 ], leading to the development of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 83%
“…Previous findings from Tanzania reported that poultry farming is associated with uncontrolled use of both human and veterinary antimicrobials, mainly for growth promotion compared to therapeutics, and metaphylaxis is very commonly practiced by the majority of farmers [ 24 , 52 ]. The level of resistance to these tested antibiotics for isolates from poultry corresponds to previous studies [ 50 , 53 , 54 ], showing poultry farming involves intensive and extensive use of antibiotics compared to other domestic animals. Tetracycline, aminoglycosides, penicillin, quinolone, and sulphonamides are among the antibiotics reported to be commonly used in poultry in Ghana, Cameroon, and Sudan [ 55 , 56 , 57 ], leading to the development of antibiotic resistance.…”
Section: Discussionsupporting
confidence: 83%
“…The antibiotic resistance of Campylobacter spp. isolated from animals in sub-Saharan Africa has already been reported [ 115 ]. This is of great concern due to frequent contact with animals that can transfer resistance genes to human Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…This study can facilitate formulating fit-for-purpose and practical control programs for the reservoir animals, and minimizing the burden of enteric infection in humans. Additionally, this is particularly important in low and middle-income countries (LMICs), where the epidemiology of these pathogens is poorly understood [ 25 ]. There are many studies that have been conducted in Bangladesh relating to the prevalence and risk factors assessment of the pathogen, including molecular detection of Campylobacter in poultry through diversified samplings; nevertheless, detection in cattle yet to be explored.…”
Section: Introductionmentioning
confidence: 99%